Chemical Kinetics of the Oxidation of Manganese and of the Decomposition of MnO2 by XRD and TG Measurements. Issue 6 (10th April 2019) - Kelzenberg, Stefan; Eisenreich, Norbert; Knapp, Sebastian; Koleczko, Andrzej; Schuppler, Heike; Fietzek, Harald
Abstract: Data from heated in‐situ X‐ray diffraction and thermogravimetry from the decomposition of MnO2 and from the oxidation of Mn are evaluated to get kinetical parameters for combustion and reaction modelling. Reaction schemes could be derived for the decomposition of MnO2 : MnO2 →Mn2 O3 →Mn3 O4 and for the oxidation of Mn: Mn→MnO→Mn3 O4 →Mn2 O3 . Different reaction models were used to fit the data and result in different kinetical parameters for the reaction steps. But comparing the results is very difficult and does not give a conclusive picture. Abstract :